2017
DOI: 10.1080/15592324.2017.1290039
|View full text |Cite
|
Sign up to set email alerts
|

Both Hsp70 chaperone and Clp protease plastidial systems are required for protection against oxidative stress

Abstract: Environmental stress conditions such as high light, extreme temperatures, salinity or drought trigger oxidative stress and eventually protein misfolding in plants. In chloroplasts, chaperone systems refold proteins after stress, while proteases degrade misfolded and aggregated proteins that cannot be refolded. We observed that reduced activity of chloroplast Hsp70 chaperone or Clp protease systems both prevented growth of Arabidopsis thaliana seedlings after treatment with the oxidative agent methyl viologen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Paraquat is widely used to study the effects of oxidative stress to isolate mutants and investigate the functions of genes involved in ROS detoxification pathways [7,[9][10][11][12][13]. In addition to SODs and other antioxidant enzymes that are part of the elaborate antioxidant defense network, plants employ various molecular strategies to counteract oxidative stress and minimize its detrimental effect, including the accumulation of osmoprotectants and compatible solutes, stress protective proteins such as late embryogenesis abundant (LEA) proteins/dehydrins, heat shock proteins (HSPs), and an activation of cellular repair mechanisms [8,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Paraquat is widely used to study the effects of oxidative stress to isolate mutants and investigate the functions of genes involved in ROS detoxification pathways [7,[9][10][11][12][13]. In addition to SODs and other antioxidant enzymes that are part of the elaborate antioxidant defense network, plants employ various molecular strategies to counteract oxidative stress and minimize its detrimental effect, including the accumulation of osmoprotectants and compatible solutes, stress protective proteins such as late embryogenesis abundant (LEA) proteins/dehydrins, heat shock proteins (HSPs), and an activation of cellular repair mechanisms [8,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, HSP70 was also identified among the proteins that were more abundant in seeds of the tolerant hybrid (Table ). HSPs 70 are chaperone proteins that bind ATP in response to stress, and they are also involved in protection against oxidative stress (Pulido, Llamas & Rodriguez‐Concepcion ). In cotton fibre, it has been demonstrated that their inhibition leads to H 2 O 2 accumulation and oxidative stress (Sable et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of the ClpC1 gene in A. thaliana reduced plant growth and hampered chloroplast development [135][136][137]. When mutants with different variations of Clp protease (clpr1, clps, clpc1, clpc1, clpd, clpt1, and clpt2) were treated with methyl viologen, clpc1 and clpc2 mutants were more resistant to methyl viologen, compared to other mutants [138]. clpc1 and clpc2 mutants show 90% similarity in DNA and amino acid sequences.…”
Section: Roles Of Clp Protease Complexes In Land Plants During Stressmentioning
confidence: 99%